Effects of joints on the reinforced rock units of fully-grouted rockbolts - Nie, Wen (2020)
A rockbolt model has been implemented into the 2-dimensional discontinuous deformation analysis (DDA-2D) code to analyze the performance of the fully grouted rockbolts installed in the jointed rock mass. Parametric studies are also conducted to investigate the effects of the rock properties, joint orientations, rockbolt lengths and in-plane spacings. The numerical study shows that the reinforcement area of the reinforcement rock unit (RRU) could be used to optimize the design of the rockbolt. The RRU induced by single rockbolt is normally in a cone shape and restrained by the orientation of the discontinuities. The RRU induced by grouped rockbolts is heavily influenced by the joint orientations and the rockbolt spacing. The design of the in-plane rockbolt spacing has to consider the joints orientations.